Risk factors for pericardial effusion after chemoradiotherapy for thoracic esophageal cancer—comparison of four-field technique and traditional two opposed fields technique. (11th April 2018) - Takata, Noriko; Kataoka, Masaaki; Hamamoto, Yasushi; Tsuruoka, Shintaro; Kanzaki, Hiromitsu; Uwatsu, Kotaro; Nagasaki, Kei; Mochizuki, Teruhito
Abstract: Pericardial effusion is an important late toxicity after concurrent chemoradiotherapy (CCRT) for locally advanced esophageal cancer. We investigated the clinical and dosimetric factors that were related to pericardial effusion among patients with thoracic esophageal cancer who were treated with definitive CCRT using the two opposed fields technique (TFT) or the four-field technique (FFT), as well as the effectiveness of FFT. During 2007–2015, 169 patients with middle and/or lower thoracic esophageal cancer received definitive CCRT, and 94 patients were evaluable (51 FFT cases and 43 TFT cases). Pericardial effusion was observed in 74 patients (79%) and appeared at 1–18.5 months (median: 5.25 months) after CCRT. The 1-year incidences of pericardial effusions were 73.2% and 76.7% in the FFT and TFT groups, respectively ( P = 0.6395). The mean doses to the pericardium were 28.6 Gy and 31.8 Gy in the FFT and TFT groups, respectively ( P = 0.0259), and the V40 Gy proportions were 33.5% and 48.2% in the FFT and TFT groups, respectively ( P < 0.0001). Grade 3 pericardial effusion was not observed in patients with a pericardial V40 Gy of <40%, or in patients who were treated using the FFT. Although the mean pericardial dose and V40 Gy in the FFT group were smaller than those in the TFT group, the incidences of pericardial effusion after CCRT were similar in both groups. As symptomatic pericardial effusion was not observed in patients with a pericardial V40 Gy of <40% or in the FFT group, it appears that FFT with a V40 Gy of <40% could help minimize symptomatic pericardial effusion.